Silvicultural treatment on Gigantochloa ligulata bamboo to increase bamboo shoot production for food consumption - Mohamed, Azmy; Maziun, Mohamed Azuan; Sulaiman, Othman; Hassan, Affendy; Wahab, Razak (2011)
In Malaysia, bamboo shoots have been relished as food since the early days. At present, bamboo shoot of Gigantochloa ligulata (buluh tumpat) is considered one of the commercial bamboo species in Malaysia. Owing to its demand as food, especially in the northern part of the country, and since there has been no study done on the thinning of this species, a study on the effect of thinning intensity as one of the silvicultural treatment on G. ligulata bamboo was conducted at Taman Wetland, Putrajaya, Malaysia. The study was done from March to June 2005. Thinning intensities of 0 % (control), 30 % and 60 % were applied twice every two months within the four months period. The three thinning intensities including the control were done in replicates and there was six replicates altogether comprising of 18 samples clumps. Thinning was based on the selection of culms three years old and above out of the total available culms within the clump. Thinning of 30% means 3 culms out of ten culms within the clump were cut. Each clump in all the replicates was applied once with 3 kg of goat dung in granule form. The organic fertilizer was applied in a circular form around the clump’s periphery. Parameters involved were number of shoots sprouted, weight of shoots and the number of culms. This included the clump expansion pattern of the selected treatment clumps. New shoots were tagged and recorded every week. A shoot which up to 30 cm and from the ground was considered as a shoot. The weights of shoots with or without sheath were recorded on a weekly basis. The distribution pattern of the shoots’ sprouting was also observed. It was found that 30% thinning intensity gave more shoots compared with other intensities including the control.